Efficacy of Tocilizumab in Patients with a Moderate and Severe COVID-19: A Retrospective Single Center Cohort Study - Sibel BOLUKÇU; Dilara KARAKUŞ; Gülay OKAY; Yasemin AKKOYUNLU; Bilge SÜMBÜL; Bülent DURDU; Meliha Meriç KOÇ; Turan ASLAN (Mediterranean Journal of Infection, Microbes and Antimicrobials)
Introduction: Interleukin-6 (IL-6) is the key cytokine in “cytokine release syndrome” and associated with the lung fibrosis. Tocilizumab (TCZ) reduces the negative effects of inflammation by blocking the binding of IL-6 to its receptor. Materials and Methods: This was a retrospective observational cohort study. Patients with microbiologically-confirmed Severe acute respiratory syndrome-Coronavirus-2 infection who received TCZ and standard treatment for Coronavirus disease-2019 (COVID‐19) were evaluated in the study. Results: A total of 64 severe and moderate COVID-19 cases were included in this study. The mean age of the patients was 57.8±13.9 years and 68.8% (n=44) of them were male, 54.7% (n=35) of them had a severe COVID-19 infection and 45.3% (n=29) of them received TCZ therapy. Standard treatment group and TCZ group were compared in terms of the mortality and clinical changes such as a fever response and need for oxygen support. Fever response was detected within the first day of the treatment in the TCZ group. Additionally, need for oxygen support was lower in the TCZ group, although the difference was not statistically significant. Admission to the intensive care unit and mortality were lower in the TCZ group. Conclusion: Efficacy of TCZ should be assessed in randomized placebo-controlled trials in the early phase of COVID-19 patients.